Haemosporidian parasites in the ash-breasted Sierra finch (Geospizopsis plebejus): insights from an Andean dry forest population. Issue 1 (8th January 2023) - Chavarría, Xavier; Matta, Nubia E.; Cadena-Ortíz, Héctor; Alarcón, Ibeth; Bahamonde-Vinueza, Daniela; González, Angie D.; Bonaccorso, Elisa
Abstract: Abstract: Haemosporidian genera Plasmodium, Haemoproteus and Leucocytozoon, responsible for avian malarial infections, are highly diverse and have a wide range of health effects and predictors, depending on the host and its environmental context. Here, we present, for the first time, detailed information on the identity, prevalence and parasitaemia of haemosporidians and other haemoparasites that infect the ash-breasted Sierra finch, Geospizopsis plebejus, in an Andean dry forest. We study the consequences of infection in the host body and health conditions and explore the environmental and intrinsic factors that influence infection status and parasitaemia. We conducted diagnoses by cytochrome b ( cytb ) sequencing and morphological identification, and estimated the levels of parasitaemia based on microscopy. We identified 6 cytb lineages infecting G. plebejus . Two of them were new lineages: Haemoproteus sp. GEPLE01 and GEPLE02. We also detected Haemoproteus sp. ZOCAP08, Haemoproteus sp. AMAVIR01, Plasmodium homopolare BAEBIC02 and Plasmodium cathemerium ZONCAP15. By microscopy, we detected Haemoproteus coatneyi, Haemoproteus erythrogravidus, P. homopolare and other unidentified species of Haemoproteus, Plasmodium, Babesia sp. and 1 microfilaria. We found no evidence of Leucocytozoon . Additionally, we detected several coinfections by sequencing and microscopy. The prevalence of haemosporidian infections was high (87.7%), and the mean parasitaemia was 61.65 infected cells per 10 000 erythrocytes examined. Prevalence and parasitaemia were higher for Haemoproteus than for Plasmodium . Haemoproteus sp. AMAVIR01 showed the highest prevalence (43.1%) and mean parasitaemia (94.39/10 000 erythrocytes) and might be associated with H. coatneyi . Immature individuals showed a lower prevalence than adults, supporting previous findings.